Microcontroller based maximum power point single axis Tracking System (Bangladesh Journal of Scientific and Industrial Research, 2013)
Positioning a photovoltaic (PV) panel in the plane of maximum irradiation can increase the power output up to 57%. An automatic microcontroller based system for maximum power point tracking (MPPT) was designed and analyzed. The system was based on positioning the PV panel perpendicular to the solar irradiation. Photosensors were used to measure the difference of solar radiation intensity among three planes. The tracking system used an 8051 microcontroller to control a stepper motor which rotated the panel towards the plane with highest radiation intensity. The MPPT system was found to be 25.9% more effective in capturing solar power than a fixed panel with the same rating. This system would be useful to increase the power output of currently operating solar panels with minor modifications in mounting. Bangladesh J. Sci. Ind. Res. 47(4), 427-432, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.4689